Fasted versus nonfasted aerobic exercise on body composition: considerations for physique athletes - Escalante, G.; Barakat, C. (Strength and Conditioning Journal, 2020)
Physique athletes often incorporate aerobic exercise as part of their exercise program to increase caloric expenditure for the purposes of improving their body composition. One method used by some physique competitors is to perform aerobic exercise in the fasted state under the assumption that low glycogen levels after an overnight fast allow for greater mobilization of stored fat to be used for fuel because carbohydrates are not readily available to produce energy. The purpose of this article is to examine the existing literature on the effect of fasted versus fed cardio on improving body composition for physique athletes.